Personal exposure to PM2.5 constituents associated with gestational blood pressure and endothelial dysfunction. (July 2019) - Xia, Bin; Zhou, Yuhan; Zhu, Qingyang; Zhao, Yingya; Wang, Ying; Ge, Wenzhen; Yang, Qing; Zhao, Yan; Wang, Pengpeng; Si, Jingyi; Luo, Ranran; Li, Jialin; et al.
Abstract: Ambient fine particulate matter (PM2.5 ) pollution has been implicated in the development of hypertensive disorders of pregnancy. However, evidence on the effects of PM2.5 -derived chemical constituents on gestational blood pressure (BP) is limited, and the potential mechanisms underlying the association remain unclear. In this study, we repeated three consecutive 72-h personal air sampling and BP measurements in 215 pregnant women for 590 visits during pregnancy. Individual PM2.5 exposure level was assessed by gravimetric method and 28 PM2.5 chemical constituents were analyzed by ED-XRF method. Plasma biomarkers of endothelial function and inflammation were measured using multiplexed immunoassays. Robust multiple linear regression models were used to estimate the associations among personal PM2.5 exposure and chemical constituents, BP changes (compared with pre-pregnancy BP) and plasma biomarkers. Mediation analyses were performed to evaluate underlying potential pathways. Result showed that exposure to PM2.5 was significantly associated with increases in systolic blood pressure (SBP), diastolic blood pressure (DBP) and mean arterial pressure (MAP) in the early second trimester. Meanwhile, elevated concentration of lead (Pb) constituent in PM2.5 was significant associated with increases in DBP and MAP after adjusting for PM2.5 total mass. PM2.5 and Pb constituent also presented positive associations with plasma biomarkers of endothelial function (ET-1, E-selectin, ICAM-1) and inflammation (IL-1β, IL-6, TNFα) significantly. After multiple adjustment, elevated ET-1 and IL-6 were significantly correlated with increased gestational BP, and respectively mediated 1.24%–25.06% and 7.01%–10.69% of the increased BP due to PM2.5 and Pb constituent exposure. In conclusion, our results suggested that personal exposure to PM2.5 and Pb constituent were significantly associated with increased BP during pregnancy, and the early second trimester might be the sensitive window of PM2.5 exposure. The endothelial dysfunction and elevated inflammation partially mediated the effect of PM2.5 and Pb constituent on BP during pregnancy. Graphical abstract: Image 1 Highlights: Exposure to PM2.5 might increase blood pressure (BP) during the early second trimester of pregnancy. PM2.5 -derived Pb constituent might increase DBP and MAP during the early second trimester of pregnancy. Endothelial dysfunction and inflammation partially mediate the elevated BP associated with PM2.5 and Pb constituent exposure. Abstract : Exposure to PM2.5 and Pb constituent could elevate gestational blood pressure via endothelial dysfunction and inflammation in women.